Community-based enterprise export strategy success: Thailands OTOP branding program - Vipada Sitabutr; Samart Deebhijarn (My University, 2017)
Thailand's One Tambon One Product (OTOP) branded handicraft and food export program in 2016 reached nearly US$3billion, with products coming from approximately 6,000 community-based enterprises (CBE) and small-medium enterprises (SME) countrywide.The OTOP movement is a global program, with communities in China, Malawi, South Africa, Thailand, Laos, and the Philippines.This study examined the influences of perceived quality, competitiveness, trust, and distribution satisfaction on entrepreneurial export performance strategy using the OTOP product brand.Structural equation modeling used LISREL Version 9.1 to conduct a confirmatory factor analysis and test the hypothesized inter-relationships on the variables influencing export performance strategy.Results showed that product quality, trust, distribution capability, and competitiveness are important factors influencing export performance strategy.It was also interesting to note that the majority of the 500 entrepreneurs (94.4%) either owned or worked in groups that had 50 or less employees.
Keywords: Innovation and Socioeconomic Development